Application of Lean Manufacturing Concepts to Evolving a Policy for Engineering Education - Armando Céspedes-Mota; Dinesh Shenoy; Leopoldo Eduardo Cárdenas-Barrón (MDPI AG, 2021)
This work analyzes the current situation of engineering education in India, especially technical universities characterized by low-quality infrastructure, inflexible curricula, and poor teaching resources including faculty, usually resulting in low student learning and very low graduate placement rates, and identifies the root causes of these problems, summarizes the methodologies adapted by previous researchers in the lean area, and applies the lean manufacturing philosophy to engineering education. This paper applies a value stream map to analyze the current state of engineering education. This technique identifies eight wastes and is given in form of a current state diagram. A future state diagram is presented that recommends solutions to eliminate these wastes. These recommendations make learning processes responsive to needs and provide long-lasting value to students. Overall, it is beneficial in developing a policy for engineering education.